Social women entrepreneurship in the Kingdom of Saudi Arabia - Florabel O. Nieva (Journal of Global Entrepreneurship Research, 2015)
Women are taking the lead as change agents and innovators in the society. The participation of women in economic activities occupied a prominent place in the list of strategic priorities and national development plans in the Kingdom of Saudi Arabia. Fostering the development of entrepreneurship sector in this country is one of the political agenda in empowering the women. Considering that the country has a very young population and a growing youth bulge a fact which leads itself well to the rise of women entrepreneurship. This paper highlights the status of social entrepreneurship in Saudi Arabia to illuminate why and how its ventures are implemented. The research objective's end view is to contribute towards the fostering of social entrepreneurship among Saudi women entrepreneurs to boost their confidence in performing the activities that create difference towards progressive development of the socio-economic frames of the country. The study focused on the social entrepreneurship activities prioritized, challenges faced by women social entrepreneurs and strategic measures recommended towards sustainable social entrepreneurship in the Kingdom. The study found out that the basic issue prioritized by social entrepreneurs was training and development; the areas of challenges met were financing, regulatory frameworks and technical support. The strategic measures recommended towards fostering social entrepreneurship in the Kingdom of Saudi Arabia were focused on access to funding, entrepreneurship culture, tax and regulation, education and training and coordinated support.
Keywords: 650; Social entrepreneurship; Women entrepreneur; Access to funding; Entrepreneurship culture; Tax and regulation; Education and training andcoordinated support